MiR-20 promotes cartilage repair in knee osteoarthritis rats via BMP2/Smad1 signaling pathway: MiR-20 in knee osteoarthritis rats - Zheng, Zhili; Wang, Dingnan; Zhang, Weiping; Yu, Han; Zhang, Yi; Feng, Ting; Zhong, Xianggen (Cellular and Molecular Biology, 2023)
To explore the effect of micro ribonucleic acid (miR)-20b on knee osteoarthritis rats by regulating the bone morphogenetic protein 2 (BMP2)/Smad1 pathway, a total of 36 SD rats were randomly divided into normal group (n=12), model group (n=12) and miR-20b mimics group (n=12). The rats in normal group were fed normally, while those in model group and miR-20b mimics group were used to establish knee osteoarthritis models. After modeling, model group was not given any intervention, but miR-20b mimics group received intra-articular injection of miR-20b mimics once a day for 2 weeks. Basso, Beattie and Bresnahan (BBB) limb motor function scoring was performed at 1, 5, 7 and 14 days after the modeling, and samples were obtained after 2 weeks of intervention. Next, hematoxylin and eosin (H&E) staining was applied to observe tissue morphology, Markin’s scoring was utilized to evaluate articular cartilage degeneration, and immunohistochemistry was employed to detect the expressions of BMP2 and Smad1. Thereafter, the expression of miR-20b was detected via qPCR, the content of cartilage oligomeric matrix protein (COMP) and C-telopeptide of type II collagen (CTX-II) was measured via enzyme-linked immunosorbent assay (ELISA), and the expressions of BMP2 and Smad1 proteins were examined via Western blotting (WB). BBB limb motor function scoring showed that compared with that in normal group, the BBB limb motor function score of rats in the other two groups was reduced (P<0.05). In comparison with that in model group, the BBB limb motor function score in miR-20b mimics group was increased from the 7th day after intervention (P<0.05). In addition, H&E staining results manifested that the articular surface in normal group was smooth and flat, with normal morphology, clear structure and no obvious damage. In model group, the articular surface was not smooth and uneven, and more articular cartilage fractures, morphological disorders and structural damages could be observed. Moreover, the articular surface in miR-20b mimics group was slightly damaged and smoother, and its morphology and structure were markedly improved in contrast to that in model group. The Markin’s score in normal group was lower than that in model group and miR-20b mimics group (P<0.05), and it was overtly decreased in miR-20b mimics group in comparison with that in model group (P<0.05). Next, immunohistochemistry demonstrated that compared with normal group, the other two groups had lowered positive expressions of BMP2 and Smad1 (P<0.05). In comparison with model group, miR-20b mimics group exhibited notably raised positive expressions of BMP2 and Smad1 (P<0.05). Then it was found from qPCR results that the expression level of miR-20b in the other two groups was overtly reduced compared with that in normal group (P<0.05), and it was prominently elevated in miR-20b mimics group in contrast to that in model group (P<0.05). Besides, ELISA illustrated that the content of COMP and CTX-II in the cartilage tissues in the other two groups was evidently reduced compared with that in normal group (P<0.05), and it was increased prominently in miR-20b mimics group compared with that in model group (P<0.05). Finally, it was revealed by WB examination that the relative expression levels of BMP2 and Smad1 proteins in the other two groups markedly declined in comparison with those in normal group (P<0.05), and they were elevated in contrast to those in model group (P<0.05). MiR-20b can promote cartilage repair and improve articular function in knee osteoarthritis rats by up-regulating the BMP2/Smad1 signaling pathway.